Development Of Fluidic-Based Memristor Sensor For Bio-Sensing Application - Mohamad Hadis, Nor Shahanim (2018)
Medical diagnosis is a crucial part of the medical field. The patient is usually required to wait for a period of time to confirm any virus infection by going through some standard laboratory procedures that require several hours or days. It is believed that fluidic-based implementation can provide fast analytical judgement on the virus infection, with short confirmation period. Looking from a sensor design perspective, the sensing area of liquid sensor cannot be exposed to its surroundings because it will cause evaporation. The fluidic-based implementation covers the sensing area from its surroundings and thus can avoid evaporation and provides an accurate result. Most of the sensor comes in a complicated structure, which requires a complex fabrication process. The developed memristor sensor is simple in structure and is fabricated using general fabrication method. Its simple structure makes this sensor more robust and easy to handle. The fluidic-based memristor sensor proposed in this study used titanium dioxide as the sensing material which sandwiched between Aluminium and Indium-Tin-Oxide as top and bottom electrodes. Three sensor structures have been designed with the third structure become the final fluidic-based structure. The second and third structures contain wells to allow more liquid to stay or as virus entrapment. The first structure was designed without any wells and applied with different pH group liquids. The result of the first structure assisted the development of the second structure, with the formation of wells and applied with liquid containing hydroxyl ion. The result of the second structure then assisted the development of the third structure and applied for dengue virus NS1 glycoprotein detection. Different wells diameters of 0.5, 1.0, 1.5 and 2.0 mm were fabricated for the third structure and the detection capabilities were investigated. All the three structure memristor sensors were characterized using current-voltage and image characterization methods. From the current-voltage characterization result, the off-on resistance ratio is extracted, and the sensing capability is determined. The second structure applied with four D-glucose concentrations, and the results show that sol-gel spin coating method recorded the highest sensitivity of 120.65 (mM)-1compared to sputtering method with the recorded sensitivity is only 0.035 (mM)-1. The sensitivity measurement recorded by the sol-gel spin coating method assists the decision for the deposition method for the third structure memristor sensor. The third structure was then applied with four dengue virus NS1 glycoprotein concentrations and the sensor with a well diameter of 2.0 mm recorded the strongest memristive behaviour with a sensitivity of 0.0082 (nM)-1, compared with another smaller diameter. The fluidic-based memristor sensor is able to detect dengue virus NS1 protein and suitable for bio-sensing application.